(untitled) (SCIENCE TIME JOURNAL, 2026)
Revolutionary changes are taking place in education today. The entry of artificial intelligence, big data, the Internet of Things (IoT), and global networks into the educational sphere has placed the question of the adequacy of traditional pedagogical theories firmly on the agenda. It is precisely in this environment that connectivism - the learning theory of the digital age - has claimed its distinctive position. Connectivism is inextricably linked with the concepts of the information society, the network society, and the knowledge economy that took shape in the second half of the twentieth century and the early twenty-first century. Rather than negating classical paradigms such as behaviourism, cognitivism, and constructivism, it takes as its subject matter a new territory they could not reach - networks, technology, and a constantly changing knowledge environment.